Vulcanized polyacrylonitrile positive electrode binder and electrode preparation method

Lithium sulfur is solved by using water-soluble cyclodextrin derivatives, linear ion-conducting polymers and metal salts in lithium sulfur batteries to buffer the volume changes of SPAN and form a fast Li+ transfer channel and efficient electron transfer path. The problems of battery stability and capacity attenuation during charging and discharging have achieved excellent rate performance and cycle stability under high load.

CN119447303AActive Publication Date: 2025-02-14INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411606944.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium-sulfur batteries, the loss of live substances and the reduction of Coulomb efficiency due to the dissolution and shuttle of the intermediate product polysulfide, affecting the stability of the battery; at the same time, the volume expansion of the vulcanized polyacrylonitrile (SPAN) during the cycle process causes the electrode deformation. The active material falls off and the battery capacity is rapidly attenuated.

Method used

The binder prepared by mixing water-soluble cyclodextrin derivatives, linear ion-conducting polymers and divalent/trivalent metal salts is used to buffer the volume changes of SPAN with supramolecular action of cyclodextrin lumen and linear polymers. A Li+ fast transfer channel is formed, and an M-S bond is formed in situ with the SPAN through the metal salt to enhance the electron conductivity.

Benefits of technology

This binder can reduce electrode powdering and shedding, accelerate ion transport and electron transport, improve battery rate performance and cycle stability, and achieve excellent performance under high load capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447303A_ABST
    Figure CN119447303A_ABST
Patent Text Reader

Abstract

The invention discloses a water-soluble binder suitable for sulfurized polyacrylonitrile (SPAN) and a preparation method of an electrode. The binder is prepared by mixing a water-soluble cyclodextrin derivative, a linear ion conduction polymer and a divalent / trivalent metal salt, the linear polymer penetrates through an inner cavity of cyclodextrin and can guide Li < + > to form directional transmission, and the transport rate of Li < + > in the thick electrode is increased; metal M ions and SPAN can form an M-S bond in situ in an electrode drying process, so that the electron conductivity of the positive electrode is improved, and the reaction kinetics of the electrode is accelerated; meanwhile, the binder can form an interpenetrating network through supramolecular interaction, and has certain self-repairing capacity, so that the volume change of the SPAN positive electrode in the charging and discharging process can be buffered, and the electrode structure is prevented from being damaged. According to the present invention, with the binder, the high-load SPAN positive electrode can be prepared, such that the problems of poor conductivity and easy active particle shedding of the SPAN positive electrode in the prior art are solved, and the multiplying power and the cycling stability of the high-load SPAN positive electrode plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium batteries, and in particular relates to a sulfurized polyacrylonitrile positive electrode binder and an electrode preparation method. Background Art

[0002] Lithium-ion batteries have been widely used in various fields, such as portable electronic products such as mobile phones, computers, and tablets, and are gradually being used in new energy vehicles, large-scale energy storage and other fields. However, the energy density of lithium-ion batteries at this stage is close to its theoretical value and cannot meet higher mileage requirements. Lithium-sulfur batteries use abundant sulfur positive electrodes (1672mAh / g) and metallic lithium negative electrodes (3860mAh / g), with a theoretical energy density of up to 2600Wh / kg, and have broad application prospects. However, lithium-sulfur batteries also have many problems in practical applications. For example, the dissolution and shuttling of polysulfides, the intermediate products of charge and discharge, lead to the loss of active substances and the reduction of coulombic efficiency, affecting the stability of the battery.

[0003] Sulfurized polyacrylonitrile (SPAN) achieves solid-solid conversion by covalently linking small molecule S to the conjugated PAN skeleton, avoiding the generation of intermediate phase polysulfides, thereby improving the battery cycle stability. However, the volume expansion of SPAN by about 40% during the cycle process may cause the electrode, especially the high-load electrode, to fall off due to excessive stress and deformation during the cycle, thereby causing the active material to decay rapidly. At the same time, the electronic conductivity of SPAN is slightly inferior to that of traditional lithium-ion battery electrode materials. The nanostructure characteristics further lead to higher tortuosity and long charge transfer distance, resulting in poor rate performance of thick electrodes and low utilization of active materials.

[0004] At present, the SPAN positive electrode loading is generally low (<6 mg / cm 2 ), when the load is increased, the pole piece is prone to cracking, falling off, or volume expansion during lithium insertion and extraction in the battery, resulting in separation of the electrode membrane from the current collector, and a significant reduction in the battery capacity. As an important component of the electrode, the binder, in addition to maintaining good electrical contact between the active material and the conductive additive, must also have excellent mechanical properties to resist deformation during electrode charging and discharging. At the same time, in thick electrodes, the binder must also have fast ion transport capabilities to improve the electrode cycle stability. Although commercial polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose-styrene butadiene rubber (CMC-SBR), etc. have high strength, their deformation adaptability is poor, making it difficult to achieve high loads and ensure high active material utilization.

[0005] Therefore, it is of great significance to develop high-performance SPAN cathode binders and accelerate the solid-solid conversion kinetics of SPAN. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sulfurized polyacrylonitrile positive electrode binder and an electrode preparation method. The binder has both bonding and ion / electronic conduction functions. On the one hand, it can buffer the volume change of SPAN during the charge and discharge process and maintain the integrity of the electrode structure. On the other hand, the linear ion conductive polymer in the binder forms Li in the inner cavity of cyclodextrin. + Fast transfer channel; in addition, the metal MS bonds formed in situ during electrode preparation accelerate electron transfer and improve the battery's rate performance and cycle stability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] One of the objectives of the present invention is to provide a binder, which is a mixture of a water-soluble cyclodextrin derivative, a linear ion-conducting polymer and a divalent / trivalent metal salt.

[0009] In the present invention, based on 100% of the total mass of the water-soluble cyclodextrin derivative, the linear ion-conducting polymer and the divalent / trivalent metal salt, the mass percentage of the cyclodextrin is 30% to 80%, and the metal salt accounts for 5% to 20% of the total mass.

[0010] In the present invention, the water-soluble cyclodextrin derivative includes cyclodextrin polymer, carbonyl cyclodextrin or a combination of the two.

[0011] In the present invention, the linear ion-conducting polymer includes one or a combination of polyacrylic acid, polyethylene oxide, and polyvinyl alcohol.

[0012] In the present invention, the divalent / trivalent metal salt cations include one or more of magnesium, calcium, iron, cobalt, nickel, copper, zinc, and aluminum; the anions include one or a combination of halide ions, sulfate ions, and nitrate ions.

[0013] The binder of the present invention is added to the SPAN positive electrode, and the supramolecular effect between the cyclodextrin inner cavity and the linear polymer can buffer the volume expansion of the SPAN positive electrode, thereby avoiding the pulverization and shedding of the electrode particles; the linear ion conductive polymer forms Li in the cyclodextrin inner cavity. + Directed transfer channels accelerate the Li + transmission; MS bonds are formed in situ between metal salts and SPAN, which improves the electronic conductivity of the electrode and accelerates the reaction kinetics.

[0014] The second object of the present invention is to provide a SPAN positive electrode sheet, wherein a water-soluble cyclodextrin derivative, a linear ion-conducting polymer and a metal salt are dissolved in deionized water, mixed evenly to obtain a binder glue solution, and then a conductive agent and SPAN particles are added, and the mixture is further mixed evenly and then coated on a conductive current collector, and the obtained positive electrode sheet is heated and dried at a heating temperature between 60 and 150° C., and the metal salt and SPAN form MS bonds in situ at high temperature.

[0015] Compared with the prior art, the present invention has the following gain effects:

[0016] The binder prepared by the present invention through water-soluble cyclodextrin derivatives, linear ion-conducting polymers and metal salts can buffer the volume expansion of SPAN particles during the charging and discharging process, thereby reducing the powdering and shedding of the electrode; the linear polymer provides Li in the cyclodextrin cavity. + Directed transmission channel accelerates ion transport; metal salt and SPAN form MS bonds in situ to improve electronic conductivity and accelerate reaction kinetics; the binder is water-soluble, the raw materials are simple and easy to obtain, it is green and environmentally friendly, and has a wide range of applications. The SPAN positive electrode prepared with the binder can achieve excellent rate performance and cycle stability under high loading. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a hardness and modulus data diagram of the SPAN positive electrode prepared in Example 1 and Comparative Example 1 obtained by nanoindentation testing.

[0018] Figure 2 It is the electronic conductivity of the SPAN positive electrode sheet described in Example 1 and Comparative Example 1.

[0019] Figure 3 The binder and SPAN positive electrode sheet described in Example 1 are 15.6 mg / cm 2 0.2C cycle effect diagram. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. Any other changes, modifications, substitutions, combinations or simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and are included in the protection scope of the present invention.

[0021] Example 1

[0022] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0023] (1) Preparation of cyclodextrin polymer: 5 g of α-cyclodextrin was added to 8 mL of 33% NaOH solution, mechanically stirred at room temperature overnight, the mixture was heated to 30°C, and then epichlorohydrin was quickly added. After stirring for 4 hours, acetone was added to terminate the reaction. Acetone was removed by decantation, and the pH was lowered to 12 with 6N hydrochloric acid, then kept at 50°C overnight, cooled, and neutralized with 6N hydrochloric acid. Finally, diafiltration was performed with a membrane with a cutoff of 3500 at a pressure of 2 bar, and the solvent was evaporated to obtain a white solid α-CDp.

[0024] (2) Preparation of the binder: 0.8 g of α-CDp, 0.15 g of polyacrylic acid and 0.05 g of copper sulfate were dissolved in deionized water, and the mixture was mixed and stirred to obtain the binder solution.

[0025] (3) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of conductive carbon black were added to the above binder solution and stirred evenly to obtain electrode slurry; the electrode slurry was coated on carbon-coated aluminum foil, dried in a forced air oven at 80° C. for 12 h, and rolled and sliced ​​to obtain SPAN positive electrode.

[0026] Example 2

[0027] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0028] (1) Preparation of cyclodextrin derivatives: 5 g of β-cyclodextrin was dissolved in 15 g of 30% H 2 O 2 The product was placed in an aqueous solution and magnetically stirred at 80°C for 24 h, and then placed in an 80°C forced air oven to evaporate the solvent to obtain a white solid C-β-CD.

[0029] (2) Preparation of binder: 0.3 g of C-β-CD, 0.5 g of polyethylene oxide and 0.2 g of magnesium nitrate were dissolved in deionized water, and the mixture was mixed and stirred to obtain the binder solution.

[0030] (3) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of Ketjen black were added to the above binder solution, and the mixture was stirred evenly to obtain an electrode slurry. The electrode slurry was coated on aluminum foil, dried in a forced air oven at 60° C. for 12 h, and rolled and sliced ​​to obtain a SPAN positive electrode.

[0031] Example 3

[0032] (1) Preparation of cyclodextrin polymer: 5 g of β-cyclodextrin was added to 8 mL of 33% NaOH solution, mechanically stirred at room temperature overnight, the mixture was heated to 30°C, and then epichlorohydrin was quickly added. After stirring for 4 hours, acetone was added to terminate the reaction. Acetone was removed by decantation, and the pH was lowered to 12 with 6N hydrochloric acid, then kept at 50°C overnight, cooled, and neutralized with 6N hydrochloric acid. Finally, diafiltration was performed with a membrane with a cutoff of 3500 at a pressure of 2 bar, and the solvent was evaporated to obtain a white solid β-CDp.

[0033] (2) Preparation of the binder: 0.8 g of β-CDp, 0.15 g of polyacrylic acid and 0.05 g of calcium chloride were dissolved in deionized water, and the mixture was mixed and stirred to obtain the binder solution.

[0034] (3) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of graphene were added to the above binder solution, and the mixture was stirred evenly to obtain an electrode slurry. The electrode slurry was coated on a carbon cloth, dried in a forced air oven at 100° C. for 12 h, and rolled and sliced ​​to obtain a SPAN positive electrode.

[0035] Example 4

[0036] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0037] (1) Preparation of cyclodextrin derivatives: 5 g of γ-cyclodextrin was dissolved in 15 g of a 30% by mass H2O2 aqueous solution and stirred magnetically at 80°C for 24 h. The product was then placed in an 80°C forced air oven to evaporate the solvent to obtain a white solid C-γ-CD.

[0038] (2) Preparation of the binder: 0.3 g of C-γ-CD, 0.5 g of polyvinyl alcohol and 0.2 g of copper nitrate were dissolved in deionized water, and the mixture was mixed and stirred to obtain the binder solution.

[0039] (3) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of carbon nanotubes were added to the above binder solution and stirred evenly to obtain electrode slurry; the electrode slurry was coated on nickel foam, dried in a forced air oven at 150° C. for 12 h, and rolled and sliced ​​to obtain SPAN positive electrode.

[0040] Comparative Example 1

[0041] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0042] (1) Preparation of binder: 0.5 g of sodium carboxymethyl cellulose was dissolved in 25 g of deionized water, and the mixture was stirred evenly. Then, 1 g of 50% by mass styrene-butadiene rubber was added, and the mixture was stirred evenly to obtain the binder solution.

[0043] (2) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of conductive carbon black were added to the above binder solution and stirred evenly to obtain electrode slurry; the electrode slurry was coated on carbon-coated aluminum foil, dried in a forced air oven at 80° C. for 12 h, and rolled and sliced ​​to obtain SPAN positive electrode.

[0044] Comparative Example 2

[0045] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0046] (1) Preparation of the binder: 1 g of polyvinylidene fluoride was dissolved in 19 g of N-methylpyrrolidone, and the mixture was mixed and stirred to obtain the binder solution.

[0047] (2) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of Ketjen black were added to the above binder solution and stirred evenly to obtain an electrode slurry; the electrode slurry was coated on a carbon-coated aluminum foil, dried in a forced air oven at 80° C. for 12 h, and rolled and sliced ​​to obtain a SPAN positive electrode.

[0048] Comparative Example 3

[0049] The method for preparing the SPAN positive electrode of this embodiment comprises the following steps:

[0050] (1) Preparation of cyclodextrin polymer: 5 g of α-cyclodextrin was added to 8 mL of 33% NaOH solution, mechanically stirred at room temperature overnight, the mixture was heated to 30°C, and then epichlorohydrin was quickly added. After stirring for 4 hours, acetone was added to terminate the reaction. Acetone was removed by decantation, and the pH was lowered to 12 with 6N hydrochloric acid, then kept at 50°C overnight, cooled, and neutralized with 6N hydrochloric acid. Finally, diafiltration was performed with a membrane with a cutoff of 3500 at a pressure of 2 bar, and the solvent was evaporated to obtain a white solid α-CDp.

[0051] (2) Preparation of the binder: 0.8 g of α-CDp and 0.2 g of polyacrylic acid were dissolved in deionized water, and the mixture was mixed and stirred to obtain the binder solution.

[0052] (3) Preparation of SPAN positive electrode: 8 g of SPAN powder and 1 g of carbon nanotubes were added to the above binder solution and stirred evenly to obtain electrode slurry; the electrode slurry was coated on aluminum foil, dried in a forced air oven at 60° C. for 12 h, and rolled and sliced ​​to obtain SPAN positive electrode.

[0053] The SPAN positive electrodes prepared in the embodiment and the comparative example were respectively assembled into batteries, and then the batteries were subjected to cycle tests at a test temperature of 25° C. and a charge-discharge voltage range of 1-3V.

Claims

1. A vulcanized polyacrylonitrile positive electrode binder, characterized in that: The binder is obtained by mixing a water-soluble cyclodextrin derivative, a linear ion-conducting polymer and a divalent / trivalent metal salt, wherein, based on the total mass of the water-soluble cyclodextrin derivative, the linear ion-conducting polymer and the metal salt as 100%, the mass percentage of the water-soluble cyclodextrin derivative is 30% to 80%, and the metal salt accounts for 5% to 20% of the total mass.

2. A vulcanized polyacrylonitrile positive electrode binder according to claim 1, characterized in that: The water-soluble cyclodextrin derivative includes one or a combination of cyclodextrin polymer and carbonyl cyclodextrin.

3. The sulfurized polyacrylonitrile positive electrode binder according to claim 1, characterized in that: The linear ion-conducting polymer includes one or a combination of polyacrylic acid, polyethylene oxide, and polyvinyl alcohol.

4. The sulfurized polyacrylonitrile positive electrode binder according to claim 1, characterized in that: The divalent / trivalent metal salt cations include one or more of magnesium, calcium, iron, cobalt, nickel, copper, zinc, and aluminum; the anions include one or a combination of halide ions, sulfate ions, and nitrate ions.

5. The method for preparing the binder according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) preparing a water-soluble cyclodextrin derivative; (2) dissolving a linear ion-conducting polymer, a divalent / trivalent metal salt and the prepared water-soluble cyclodextrin derivative in deionized water in a certain proportion, and mixing and stirring the mixture evenly.

6. A sulfurized polyacrylonitrile positive electrode, characterized in that: The sulfide polyacrylonitrile positive electrode includes a conductive current collector and a positive electrode film adhered to at least one side of the current collector, and the positive electrode film includes 80% to 96% by mass of sulfide polyacrylonitrile positive electrode material, 2% to 10% of a conductive agent and 2% to 10% of a binder as described in any one of claims 1 to 4.

7. The method for preparing the sulfurized polyacrylonitrile positive electrode according to claim 6, characterized in that: The preparation method comprises the following steps: (1) mixing a water-soluble cyclodextrin derivative, a linear ion-conducting polymer, and a divalent / trivalent metal salt in a certain mass ratio and dissolving them in deionized water to obtain a glue solution; (2) adding polyacrylonitrile sulfide and a conductive agent to the above-mentioned glue solution, adding an appropriate amount of deionized water, and stirring evenly to obtain a positive electrode slurry; (3) The positive electrode slurry is uniformly coated on a conductive current collector and dried at 60 to 150° C. to obtain a sulfurized polyacrylonitrile positive electrode.

Citation Information

Patent Citations

  • Nitrogen-containing binder for sulfur-lithium batteries and preparation method thereof

    CN106159272A

  • Ether electrolyte and lithium-sulfur secondary battery

    CN110416597A

  • Lithium-sulfur battery sulfur-based positive electrode binder, sulfur-based positive electrode and preparation method of sulfur-based positive electrode

    CN115207358A